Battery positive electrode material and preparation method and application thereof

By combining vanadium trioxide with carbon to form composite nanomaterials and forming heterojunctions, the problems of poor conductivity of vanadium oxides and slow ion transport are solved, and the rate performance and cycling performance of the battery are significantly improved.

CN114597390BActive Publication Date: 2025-04-25SHENZHEN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210131280.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-02-11
Publication Date
2025-04-25
Estimated Expiration
2042-02-11

AI Technical Summary

Technical Problem

Vanadium oxides have poor conductivity and slow ion transmission rates in battery applications, which limit the rate performance of the battery.

Method used

A composite nanomaterial of vanadium trioxide and carbon is used to improve conductivity and ion transport capability by forming heterojunctions.

Benefits of technology

The conductivity and ion transmission rate of the battery positive electrode material are significantly improved, and the rate performance and cycling performance of the secondary battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114597390B_ABST
    Figure CN114597390B_ABST
Patent Text Reader

Abstract

The present application provides a battery positive electrode material and a preparation method and application thereof, wherein the battery positive electrode material comprises a composite nanomaterial of vanadium trioxide and carbon, wherein the composite nanomaterial comprises a heterojunction formed by vanadium trioxide and carbon. The battery positive electrode material has good electrical conductivity and ion transport capability, and its application in a battery is conducive to optimizing the rate performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to battery positive electrode materials and preparation methods and applications thereof. Background Art

[0002] With the aggravation of energy crisis and environmental pollution, it is particularly important to develop green and clean energy storage devices. Vanadium oxides have been widely used in electrochemical research due to their low cost, high crustal reserves, and high theoretical specific capacity. However, vanadium oxides have poor conductivity and slow ion transfer rate, which is not conducive to the rate performance of batteries. Therefore, it is necessary to provide a new battery positive electrode material to improve the ion and electron transfer efficiency of battery positive electrode materials and improve the electrochemical performance of batteries. Summary of the invention

[0003] In view of this, the present application provides a battery positive electrode material, which has good conductivity and ion transport capability, and its application in batteries is beneficial to improving the rate performance of the battery.

[0004] In a first aspect, the present application provides a positive electrode material for a battery, comprising a composite nanomaterial of vanadium trioxide and carbon, wherein the composite nanomaterial comprises a heterojunction formed by vanadium trioxide and carbon.

[0005] The battery positive electrode material of the present application includes a composite nanomaterial composed of vanadium trioxide and carbon, wherein vanadium trioxide and carbon form a heterojunction, which can effectively improve the conductivity of the positive electrode material and optimize the ion transmission path, so that active ions can migrate quickly in the material, thereby obtaining good ion and electron transmission performance, thereby improving the rate performance of the secondary battery.

[0006] Optionally, the vanadium trioxide belongs to the trigonal crystal system.

[0007] Optionally, the space group of the vanadium trioxide is R-3c.

[0008] Optionally, in the composite nanomaterial, the mass percentage of the carbon is 0.1% to 10%.

[0009] Optionally, the composite nanomaterial is a sheet-like structure, and the thickness of the composite nanomaterial is 1 nm to 30 nm.

[0010] Optionally, the size of the heterojunction is 2nm to 20nm.

[0011] In a second aspect, the present application provides a method for preparing a positive electrode material for a battery, comprising:

[0012] Etching MAX phase powder to obtain V2CT x ;

[0013] The V2CT x After mixing with an oxidant, carbon-doped vanadium oxide is obtained, and the carbon-doped vanadium oxide is annealed in a reducing atmosphere to obtain the battery positive electrode material. The battery positive electrode material includes a composite nanomaterial of vanadium trioxide and carbon, and the composite nanomaterial includes a heterojunction formed by vanadium trioxide and carbon.

[0014] Optionally, the MAX phase powder includes one or more of V2AlC, V2SiC, V2PC, V2GaC, V2GeC, V2AsC, V2InC, V2SnC, and V2PbC.

[0015] Optionally, the etching comprises: mixing the MAX phase powder with an etchant, and obtaining V2CT after a hydrothermal reaction. x .

[0016] Optionally, the etchant includes one or more of hydrofluoric acid, hydrochloric acid and lithium fluoride, hydrochloric acid and sodium fluoride, hydrochloric acid and potassium fluoride, hydrochloric acid and zinc fluoride, hydrochloric acid and aluminum fluoride, and hydrochloric acid and calcium fluoride.

[0017] Optionally, the temperature of the hydrothermal reaction is 80° C. to 160° C., and the time of the hydrothermal reaction is 12 h to 48 h.

[0018] Optionally, the oxidant comprises hydrogen peroxide; the V2CT x The mass ratio of the hydrogen peroxide to the hydrogen peroxide is 1:(0.5-5).

[0019] Optionally, the V2CT x The mixing time with the oxidant is 5min to 20min.

[0020] Optionally, the preparation method further comprises: freeze-drying the carbon-doped vanadium oxide before the annealing treatment.

[0021] Optionally, the freeze-drying temperature is -25°C to -5°C, and the freeze-drying time is 36h to 72h.

[0022] Optionally, the temperature of the annealing treatment is 700° C. to 1000° C., and the time of the annealing treatment is 0.5 h to 4 h.

[0023] Optionally, the reducing atmosphere comprises a reducing gas and an inert gas, and the volume percentage of the reducing gas in the reducing atmosphere is 2% to 15%.

[0024] The preparation method of the battery positive electrode material provided in the present application has a simple and controllable process and is easy to operate. The obtained battery positive electrode material has good conductivity and ion transfer rate. Applying it in a battery can make the battery have good rate performance.

[0025] In a third aspect, the present application provides a secondary battery comprising a positive electrode, a negative electrode, an electrolyte, and a separator located between the positive electrode and the negative electrode, wherein the positive electrode comprises the battery positive electrode material described in the first aspect of the present application or the battery positive electrode material obtained by the preparation method described in the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 V2CT in Example 1 of this application x -SEM image of MXene;

[0027] Figure 2 This is a scanning electron microscope image of the composite nanomaterial in Example 1 of the present application;

[0028] Figure 3 This is the element distribution diagram of the composite nanomaterial in Example 1 of the present application;

[0029] Figure 4 This is a transmission electron microscope image of the composite nanomaterial in Example 1 of the present application;

[0030] Figure 5 This is a characterization diagram of the heterojunction of the composite nanomaterial in Example 1 of the present application;

[0031] Figure 6 This is a thickness characterization diagram of the composite nanomaterial in Example 1 of the present application;

[0032] Figure 7 This is a thermogravimetric analysis diagram of the composite nanomaterial in Example 1 of the present application;

[0033] Figure 8 XRD comparison diagram of the composite nanomaterial of Example 1 of the present application, the positive electrode material of Comparative Example 1 and Comparative Example 2, and V2O3 of the trigonal phase;

[0034] Fig. 9 This is a cycle performance diagram of the secondary battery of Example 1 of the present application;

[0035] Fig.10 This is a rate performance diagram of the secondary battery of Example 1 of the present application. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0037] At present, lithium-ion batteries are widely used in the field of energy storage. However, lithium-ion batteries are limited in their large-scale application in the future due to the shortage and uneven distribution of lithium resources, poor battery safety, toxicity and environmental pollution caused by organic systems. Compared with lithium-ion batteries, zinc-ion batteries use aqueous electrolytes, which have the advantages of high safety, environmental friendliness, low cost, and easy assembly. In addition, zinc-ion batteries have high energy density and abundant reserves of battery raw materials, making them have high application value and development prospects in the field of energy storage. However, zinc-ion batteries are limited in their large-scale application due to their poor rate performance. Therefore, it is necessary to develop a positive electrode material for zinc-ion batteries with good rate performance.

[0038] The present application provides a positive electrode material for a battery, which includes vanadium trioxide and a carbon composite nanomaterial (V2O3 and C composite nanomaterial), wherein carbon and vanadium trioxide coexist and form a heterojunction. The present application combines vanadium trioxide with carbon to form a composite nanomaterial with a heterojunction, and the heterojunction can improve the conductivity of the positive electrode material of the battery and improve the migration performance of zinc ions in the positive electrode material.

[0039] In the V2O3 and C composite nanomaterials of the present application, the valence state of vanadium in vanadium trioxide is relatively low (+3), and its relatively low valence state enables it to have a higher theoretical capacity as a positive electrode material, with a maximum theoretical capacity of up to 715 mAh / g; on the other hand, vanadium trioxide has abundant oxygen vacancies, which is beneficial for the positive electrode material to provide more active sites and diffusion paths for the embedding of zinc ions. The presence of a carbon-containing heterojunction structure can ensure good electronic conductivity, increase the electron transmission rate, and accelerate the migration of zinc ions, thereby improving the rate performance of the battery positive electrode material. In some embodiments of the present application, vanadium trioxide belongs to the trigonal system and has a hexagonal close-packed crystal structure. In the trigonal system of vanadium trioxide, vanadium atoms are connected into bonds and form a zigzag VV chain, and the vanadium atoms V 3d The electrons in the orbit can move freely along the VV chain and have a distinct electronic state at the Fermi level, which makes the positive electrode material of the battery have intrinsic metallic behavior and good electron transfer ability; and the VV chain and oxygen atoms are interwoven to form a three-dimensional skeleton, and the structure of the three-dimensional skeleton is an open tunnel structure, which is conducive to the diffusion of zinc ions in the positive electrode material, thereby increasing the migration rate of ions. In some embodiments of the present application, the space group of vanadium trioxide is R-3c.

[0040] In the embodiment of the present application, vanadium trioxide and carbon form a composite nanomaterial with a heterojunction, the carbon in the positive electrode material can improve the conductivity of the positive electrode material, and the heterojunction formed by carbon and vanadium trioxide can reduce the diffusion barrier of zinc ions in the positive electrode material, promote the transmission of zinc ions in the positive electrode material, and optimize the transmission path of ions and electrons, increase the migration rate of ions and electrons, so that the battery can obtain good rate performance. In addition, the heterojunction can improve the structural stability of the vanadium trioxide tunnel skeleton, inhibit the lattice change of the tunnel skeleton during the zinc ion embedding and de-embedding process, enhance the firmness of the tunnel skeleton lattice, and make the battery have good cycle performance.

[0041] In some embodiments of the present application, the mass percentage of carbon in the V2O3 and C composite nanomaterials is 0.1% to 10%. The mass percentage of carbon in the V2O3 and C composite nanomaterials can be, but is not limited to, 0.1%, 0.3%, 0.5%, 1%, 3%, 5%, 8%, and 10%. Controlling the carbon content is conducive to the formation of more heterojunctions between carbon and vanadium trioxide, thereby effectively improving the ion and electron transmission efficiency of the battery positive electrode material and improving the electrochemical performance of the battery. In some embodiments of the present application, the mass percentage of carbon in the V2O3 and C composite nanomaterials is 0.3% to 7%.

[0042] In some embodiments of the present application, the V2O3 and C composite nanomaterials are sheet structures, and the composite nanomaterials include nanosheets. The nanosheet structure is beneficial to increase the contact area between the positive electrode material and the electrolyte, and improve the transmission performance of ions and electrons. In some embodiments of the present application, the thickness of the V2O3 and C composite nanomaterials is 1nm to 30nm. The thickness of the V2O3 and C composite nanomaterials can be, but not limited to, 1nm, 5nm, 10nm, 15nm, 20nm or 30nm. In some embodiments of the present application, the thickness of the V2O3 and C composite nanomaterials is 1nm to 15nm. When the thickness of the composite nanomaterial is small, it is beneficial to increase the diffusion rate of ions and improve the rate performance of the battery. In some embodiments of the present application, the size of the heterojunction is 2nm to 20nm. The size of the heterojunction can be, but not limited to, 2nm, 4nm, 8nm, 10nm, 15nm or 20nm. In some embodiments of the present application, the pore size of the tunnel structure of the V2O3 and C composite nanomaterial is 0.2nm to 0.5nm, and the pore size of the tunnel structure can be, but is not limited to, 0.2nm, 0.25nm, 0.28nm, 0.3nm, 0.4nm or 0.5nm. The tunnel structure of this size has good adaptability to zinc ions and is conducive to the migration of zinc ions in the positive electrode material.

[0043] The present application combines carbon with vanadium trioxide to form a composite nanomaterial and applies it as a positive electrode material in a secondary battery. The positive electrode material has good ion and electron transmission performance and structural stability, which is beneficial to improving the rate performance and cycle performance of the secondary battery.

[0044] The present application also provides a method for preparing the above-mentioned battery positive electrode material, comprising the following steps:

[0045] Step 100: Etching the MAX phase powder to obtain V2CT x ;

[0046] Step 200: V2CT x After being mixed with an oxidant and dried, the battery positive electrode material is obtained after annealing in a reducing atmosphere.

[0047] In step 100 of the present application, the MAX phase powder is etched by hydrogen fluoride etching to obtain V2CT x MAX phase material is a layered compound composed of three elements, and its general chemical formula is expressed as M n+1 AX n , M represents a transition metal element (vanadium, V in this application), A represents a main group element, X represents carbon or nitrogen (carbon, C in this application), n = 1, 2, 3 ..., V2CT x It is two-dimensional vanadium carbide, and T in the molecular formula refers to the surface group of the two-dimensional material (such as O, OH, F, NH, etc.). In the embodiment of the present application, the MAX phase powder includes one or more of V2AlC, V2SiC, V2PC, V2GaC, V2GeC, V2AsC, V2InC, V2SnC, and V2PbC. The present application etches the main group elements in the MAX phase powder with hydrogen fluoride to obtain two-dimensional vanadium carbide. The two-dimensional vanadium carbide has a series of unique properties, such as high metallic conductivity, excellent dispersion quality, rich surface groups, etc. Using it as a precursor is beneficial to the preparation of vanadium trioxide and carbon composite nanomaterials with high crystallinity and unique heterojunction structure in the subsequent process.

[0048] In some embodiments of the present application, the MAX phase powder is etched to obtain V2CT x include:

[0049] Mix the MAX phase powder with the etchant and obtain V2CT after hydrothermal reaction. x , wherein the etchant includes one or more of hydrofluoric acid, hydrochloric acid and lithium fluoride, hydrochloric acid and sodium fluoride, hydrochloric acid and potassium fluoride, hydrochloric acid and zinc fluoride, hydrochloric acid and aluminum fluoride, hydrochloric acid and calcium fluoride; the temperature of the hydrothermal reaction is 80° C. to 160° C., and the time of the hydrothermal reaction is 12 h to 48 h.

[0050] The MAX phase powder can be etched using the above method to obtain an accordion-shaped V2CT x , the accordion-shaped V2CT x It can provide a two-dimensional framework for the formation of composite nanomaterials, which is conducive to the construction of an ordered open tunnel structure in the V2O3 and C composite nanomaterials, thereby improving the ion and electron transport performance of the positive electrode material. In some embodiments of the present application, the temperature of the hydrothermal reaction during etching is 100°C to 140°C, and the time of the hydrothermal reaction is 20h to 40h.

[0051] In some embodiments of the present application, hydrochloric acid and lithium fluoride are used as etchants to etch the MAX phase powder to obtain an accordion-shaped V2CT x The specific preparation method includes: adding MAX phase powder to a mixed solution of hydrochloric acid and lithium fluoride, stirring for 10 minutes to 60 minutes, transferring the solution to a stainless steel autoclave lined with polytetrafluoroethylene, reacting at 80°C to 160°C for 12 hours to 48 hours, centrifuging the reaction solution to collect the precipitate, washing the precipitate and vacuum drying it at 50°C to 70°C for 1 hour to 20 hours to obtain an accordion-shaped V2CT x . In some embodiments of the present application, the MAX phase powder includes V2AlC, and the aluminum in V2AlC is easily etched, which is beneficial to improving the efficiency of the reaction. In some embodiments of the present application, in the mixed solution of hydrochloric acid and lithium fluoride, the mass ratio of lithium fluoride to hydrochloric acid is 1: (4-8). In some embodiments of the present application, the mass ratio of MAX phase powder, lithium fluoride and hydrochloric acid is 1: (1.5-3): (6-24). In some embodiments of the present application, the mixed solution of hydrochloric acid and lithium fluoride is obtained by dispersing 1g-3g of LiF into 10mL-50mL of hydrochloric acid with a concentration of 6mol / L-12mol / L. In some embodiments of the present application, after the reaction solution is centrifuged to collect the precipitate, the precipitate can be washed by first washing with water until the pH of the supernatant is neutral, and then washing with ethanol, so that V2CT x Has higher purity.

[0052] In step 200 of the present application, V2CT x After mixing with the oxidant, the oxidant will destroy the chemical bonds between carbon atoms and vanadium atoms and oxidize the vanadium into high-valent vanadium oxide to obtain carbon-doped vanadium oxide. The carbon-doped vanadium oxide is then annealed in a reducing atmosphere to obtain vanadium trioxide and carbon composite nanomaterials.

[0053] In some embodiments of the present application, the oxidant includes hydrogen peroxide, and V2CT x Mixing with hydrogen peroxide can be: V2CT x Dispersed in water to obtain V2CT with a concentration of 1g / L to 4g / L xAqueous dispersion, then V2CT x A hydrogen peroxide solution is added to the aqueous dispersion, and the mass percentage of hydrogen peroxide in the hydrogen peroxide solution is 1% to 30%. In some embodiments of the present application, V2CT x The mass ratio of V2CT to hydrogen peroxide is 1:(0.5~5). x The mass ratio of V2CT to hydrogen peroxide can be, but is not limited to, 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:2, 1:2.5, 1:3, 1:4 or 1:5. x The oxidant is mixed by stirring at a speed of 300 rpm to 600 rpm for 5 to 20 minutes. Controlling the stirring speed and time is conducive to the oxidant's moderate oxidation of vanadium, thereby improving the purity of the composite nanomaterial of vanadium trioxide and carbon obtained subsequently.

[0054] In some embodiments of the present application, V2CT x After mixing with an oxidant, a carbon-doped vanadium oxide is obtained, and then the carbon-doped vanadium oxide is freeze-dried to remove moisture and impurities in the vanadium oxide. The freeze-drying method can reduce the influence of the external environment on the carbon-doped vanadium oxide and inhibit changes in the product morphology and internal structure. In some embodiments of the present application, the freeze-drying temperature is -25°C to -5°C, and the freeze-drying time is 36h to 72h.

[0055] In the present application, when the carbon-doped vanadium oxide is annealed in a reducing atmosphere, the high-valent vanadium oxide is converted into vanadium trioxide, and the vanadium trioxide forms a heterojunction with carbon. In some embodiments of the present application, the temperature of the annealing treatment is 700°C to 1000°C, and the annealing time is 0.5h to 4h. The temperature of the annealing treatment may be, but is not limited to, 700°C, 750°C, 800°C, 850°C, 900°C or 1000°C, and the annealing time may be, but is not limited to, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h or 4h. Controlling the temperature and time of the annealing treatment is conducive to the formation of a structurally stable vanadium trioxide and carbon composite nanomaterial, and inhibiting the reduction of carbon, ensuring that the material has good electrical conductivity. In some embodiments of the present application, the heating rate of the annealing process is 1°C / min to 10°C / min. In some embodiments of the present application, the reducing atmosphere includes a reducing gas and an inert gas, and the volume percentage of the reducing gas in the reducing atmosphere is 2% to 15%. The volume percentage of the reducing gas in the reducing atmosphere can be, but is not limited to, 2%, 3%, 5%, 7%, 10%, 12% or 15%. Controlling the content of the reducing gas is conducive to fully converting the carbon-doped vanadium oxide into a composite nanomaterial of vanadium trioxide and carbon. In some embodiments of the present application, the inert gas can be one or more of nitrogen, helium, argon and hydrogen, and the reducing gas can be hydrogen. In the embodiments of the present application, the annealing equipment can be any one of a rotary furnace, a rotary furnace, a box furnace, a tubular furnace, a roller kiln, a push plate kiln or a fluidized bed.

[0056] The preparation method provided in this application is simple and easy to implement. x Vanadium trioxide and carbon composite nanomaterials are obtained as precursors and processed by specific processes. The resulting material has high electrical conductivity and ion transfer rate. Its application in batteries is beneficial to improving the battery's rate performance.

[0057] The present application also provides a positive electrode sheet, which includes a current collector and a positive electrode material layer disposed on the current collector, wherein the positive electrode material layer includes the battery positive electrode material of the present application. In the present application, the preparation of the positive electrode material layer can be to mix the battery positive electrode material, the conductive agent, the binder and the solvent to form a positive electrode slurry, and the positive electrode slurry is coated and dried to obtain the positive electrode material layer. Among them, the conductive agent, the binder and the solvent are conventional choices in the field of batteries. For example, the binder can be selected from one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC) and sodium alginate. The conductive agent can be selected from one or more of carbon nanotubes, acetylene black and graphene.

[0058] The present application also provides a secondary battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator located between the positive electrode and the negative electrode, wherein the positive electrode comprises the battery positive electrode plate provided in the present application.

[0059] In some embodiments of the present application, the negative electrode may include a metal zinc sheet or a zinc alloy sheet. In some embodiments of the present application, the separator may be one or more of a polyolefin microporous membrane, a polyethylene non-woven fabric-based membrane, a polypropylene-based membrane, and a glass fiber-based membrane.

[0060] In the present application, the electrolyte of the secondary battery includes a zinc salt aqueous solution. In the embodiment of the present application, the zinc salt can be one or more of Zn(OTF)2 (zinc trifluoromethanesulfonate), zinc perchlorate, zinc sulfate, zinc chloride, and zinc acetate. In the embodiment of the present application, the concentration of the zinc salt in the electrolyte is 0.1mol / L to 15mol / L. In some embodiments of the present application, the concentration of the zinc salt in the electrolyte is 1mol / L to 4mol / L.

[0061] The secondary battery provided in the present application has good rate performance and cycle performance due to the use of the battery positive electrode material of the present application.

[0062] The present application also provides an electronic device, which includes the secondary battery.

[0063] The technical solution of the present application is further described below with reference to a number of embodiments.

[0064] Example 1

[0065] 1) A preparation method of a positive electrode material for a battery, comprising:

[0066] V2CT x Preparation of -MXene: 1.0g V2AlC powder was slowly added to LiF and HCl solution (2.0g LiF was dispersed in 30mL HCl with a concentration of 12mol / L) within 10min. After stirring at room temperature for 30min, the solution was transferred to a 50mL polytetrafluoroethylene-lined stainless steel autoclave and sealed at 120°C for reaction for 36h. The turbid suspension obtained after the reaction was centrifuged to collect the precipitate, washed with water and centrifuged, and washed repeatedly until the pH of the supernatant was neutral. The precipitate was further washed with ethanol and vacuum dried at 60°C for 12h to obtain V2CT. x -MXene.

[0067] Preparation of vanadium trioxide and carbon composite nanomaterials: 0.2 g of V2CT x -MXene was dispersed in 100 mL of water to obtain a V2CT concentration of 2 mg / mL x-MXene suspension, V2CT x -MXene suspension was added dropwise with 2 mL of 30 wt% H2O2 aqueous solution under strong stirring. After continuous stirring for 10 min, the solution was immersed in liquid nitrogen for freezing. The frozen solution was transferred to a vacuum freeze dryer for freeze drying for 48 h. The obtained powder was ground and placed in a tubular furnace. In an Ar / H2 (95 / 5, vol / vol) atmosphere, it was annealed at 800°C for 2 h at a heating rate of 5°C / min to obtain V2O3 and C composite nanomaterials.

[0068] 2) Preparation of secondary batteries:

[0069] Preparation of battery positive electrode: V2O3 and C composite nanomaterials are mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 7:2:1, and after being fully ground in an agate mortar, an appropriate amount of N-methylpyrrolidone is added, and the mixture is stirred in a dispersion and degassing mixer for 15 minutes to obtain a positive electrode slurry. The positive electrode slurry is coated on the surface of a titanium foil with a thickness of 0.01 mm with a scraper (100 μm) and dried under vacuum conditions to prepare a positive electrode sheet. The positive electrode sheet is cut into discs with a diameter of 12 mm as the positive electrode.

[0070] Preparation of electrolyte: Water and polyethylene glycol (400 mesh) were mixed in a mass ratio of 1:1 as a solvent to prepare a Zn(OTF)2 solution with a concentration of 3 mol / L as the electrolyte.

[0071] Preparation of the battery: A zinc foil disc with a diameter of 14 mm and a thickness of 0.1 mm is used as the negative electrode, and a glass fiber separator is used as the separator. The positive electrode, the negative electrode, and the separator are assembled into a battery cell, and an electrolyte is injected to obtain a secondary battery.

[0072] Comparative Example 1

[0073] A preparation method of a positive electrode material, comprising:

[0074] 1.0 g of V2AlC powder was slowly added to LiF and HCl solution (2.0 g of LiF was dispersed in 30 mL of 12 mol / L HCl) within 10 min. After stirring at room temperature for 30 min, the solution was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and sealed at 120 ° C for 36 h. The turbid suspension obtained after the reaction was centrifuged to collect the precipitate, washed with water and centrifuged, and the washing was repeated until the pH of the supernatant was neutral. The precipitate was further washed with ethanol and vacuum dried at 60 ° C for 12 h to obtain V2CT. x -MXene.

[0075] 0.2 g of V2CT xAfter the MXene was fully ground, the obtained powder was placed in a tube furnace and annealed at 800°C for 2h at a heating rate of 5°C / min in an Ar / H2 (95 / 5, vol / vol) atmosphere to obtain a positive electrode material. A battery was prepared in the same manner as in Example 1.

[0076] Comparative Example 2

[0077] The difference between Comparative Example 2 and Comparative Example 1 is that the positive electrode material in Comparative Example 2 is prepared by the following method:

[0078] 0.2 g of V2CT x -MXene was dispersed in 100 mL of water to obtain a V2CT concentration of 2 mg / mL x -MXene suspension, V2CT x -MXene suspension was added dropwise with 2 mL of 30 wt% H2O2 aqueous solution under strong stirring, and the solution was immersed in liquid nitrogen for freezing after continuous stirring for 10 min. The frozen solution was transferred to a vacuum freeze dryer for freeze drying for 48 h. The obtained powder was ground and placed in a tube furnace. Under nitrogen atmosphere, it was annealed at 800 ° C for 2 h at a heating rate of 5 ° C / min to obtain a positive electrode material. The battery was prepared in the same manner as in Example 1.

[0079] Effect Example

[0080] In order to verify the structure and performance of the battery positive electrode material prepared in the present application, the present application also provides an effect embodiment.

[0081] 1) The morphology of the material was characterized using a field emission electron microscope (model: JSM-7800F & TEAM Octane Plus), see Figure 1 , Figure 1 V2CT in Example 1 of this application x -SEM image of MXene, by Figure 1 It can be seen that V2CT x -MXene has an accordion-like morphology and a distinct layered structure. Figure 2 , Figure 2 is a scanning electron microscope image of the composite nanomaterial in Example 1 of the present application, Figure 2 It can be seen that the composite nanomaterial includes multiple nanosheets, which are stacked to form a layered structure. Figure 2 From the perspective of the field emission scanning electron microscope combined with EDS spectrometer, the element distribution of the composite nanomaterials was characterized. Figure 3 is the element distribution diagram of the composite nanomaterial in Example 1 of the present application, Figure 3It can be seen that the C element, V element and O element are evenly distributed in the material.

[0082] The morphology of the material was characterized by a high-resolution transmission electron microscope (model: Tecnai G2 F30). Figure 4 , Figure 4 is a transmission electron microscope image of the composite nanomaterial in Example 1 of the present application, Figure 4 It can be seen that the composite nanomaterial presents an obvious two-dimensional layered structure. Figure 5 , Figure 5 This is a characterization diagram of the heterojunction of the composite nanomaterial in Example 1 of the present application, Figure 5 It can be seen that a heterojunction is formed between carbon and vanadium trioxide (V2O3) in the composite nanomaterial. The thickness of the nanosheets in the composite nanomaterial was characterized using an atomic force microscope (Model: Dimension Edge, Bruker, America). Figure 6 , Figure 6 This is a thickness characterization diagram of the composite nanomaterial in Example 1 of the present application. Figure 6 It can be seen that the thickness of the V2O3 and C heterojunction nanosheets is 5 nm.

[0083] 2) The carbon content in the composite nanomaterial in Example 1 was analyzed using a thermogravimetric analyzer. Figure 7 , Figure 7 is the thermogravimetric analysis diagram of the composite nanomaterial in Example 1 of the present application, Figure 7 The mass percentage of carbon in the composite nanomaterial can be calculated. Specifically, when the V2O3 and C composite nanomaterial is calcined in an air atmosphere, the crystalline water molecules and carbon in the material will form gas and leave the material, and V2O3 will be oxidized to V2O5. Fig. 9 The mass loss of the composite nanomaterial before 110°C is the release of crystal water molecules, and its mass loss G H2O It is about 0.43%. The mass fraction increment caused by V2O3 oxidation can be calculated according to the following formula: That is, the mass change caused by the oxidation of V2O3 G re is 21.3%, so the mass loss of carbon G c It can be calculated according to the following relationship:

[0084] G c % = 121.32% - G H2O %-G re %

[0085] In the above formula, G c % represents the mass fraction of carbon content, G H2O % represents the mass fraction of water, G re% represents the residual mass fraction. The mass percentage of carbon in the composite nanomaterial is calculated as follows: c % = 121.32% - 0.43% - 116.97% = 3.65%. That is, the carbon content in the composite nanomaterial in Example 1 is 3.65%.

[0086] 3) X-ray diffractometer (model: Bruker, D8 Advance with Cu-Kαradiation) was used to characterize the phase structure of the material. Figure 8 , Figure 8 This is an XRD comparison diagram of the composite nanomaterial of Example 1 of the present application, the positive electrode material of Comparative Example 1 and Comparative Example 2, and V2O3 of the trigonal phase, Figure 8 In the figure, the curves from top to bottom are respectively the XRD characterization curve of the positive electrode material of Comparative Example 2, the XRD characterization curve of the positive electrode material of Comparative Example 1, the XRD characterization curve of the composite nanomaterial of Example 1, and the standard curve of V2O3 of the trigonal phase (PDF#71-345). Figure 8 It can be seen that the composite nanomaterial in Example 1 is consistent with the V2O3 characterization curve of the trigonal phase, indicating that the V2O3 in the composite nanomaterial of the present application belongs to the trigonal system. However, the positive electrode materials prepared in Comparative Examples 1 and 2 have completely different structures from those in Example 1, and the V2O3 and C composite nanomaterials of the present application are not obtained.

[0087] 4) The electrochemical properties of the secondary battery of Example 1 were tested using a Blue Electric test system (model: CT2001A, Wuhan Blue Electric Co., Ltd.) and an electrochemical workstation (model: IVIUMnSTAT, IVIUM, the Netherlands). The specific test conditions were as follows: the battery was charged to 1.7 V at a constant current of 10 A / g at room temperature, and then discharged to 0.2 V at a constant current of 10 A / g, and the discharge capacity and charge capacity of the battery were recorded. After repeated charge and discharge cycles for 16,000 times, the discharge capacity of the 16,000th cycle was recorded, and the capacity retention rate after the cycle was calculated.

[0088] See also Fig. 9 , Fig. 9 is a cycle performance diagram of the secondary battery of Example 1 of the present application, Fig. 9 It can be seen that the specific capacity of the secondary battery of Example 1 is close to 200 mAh / g at a current density of 10 A / g, and the capacity is still 120 mAh / g after 16,000 cycles. From the specific capacity and capacity retention rate test of the secondary battery, it can be seen that the secondary battery provided by the present application has a high specific capacity and cycle stability.

[0089] See also Fig.10 , Fig.10 is a rate performance diagram of the secondary battery of Example 1 of the present application, Fig.10 It can be seen that the secondary battery of Example 1 can recover its specific capacity to the initial value at the same current density after 50 cycles at different current densities, that is, it has good reversibility, and even at a high current density of 20A / g, its specific capacity can be close to 100mAh / g, which shows that the battery positive electrode material of the present application can have high rate performance and good cycle stability.

[0090] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A battery positive electrode material, characterized in that: A composite nanomaterial comprising vanadium trioxide and carbon, wherein the composite nanomaterial comprises a heterojunction formed by vanadium trioxide and carbon, and the vanadium trioxide belongs to a trigonal system; The preparation of the battery positive electrode material comprises: etching the MAX phase powder to obtain V2CT x , the V2CT x The carbon-doped vanadium oxide is mixed with an oxidant to obtain a carbon-doped vanadium oxide, and the carbon-doped vanadium oxide is annealed in a reducing atmosphere to obtain the battery positive electrode material.

2. The battery positive electrode material according to claim 1, characterized in that In the composite nano material, the mass percentage of the carbon is 0.1% to 10%.

3. The battery positive electrode material according to claim 1 or 2, characterized in that: The composite nano material is a sheet-like structure, and the thickness of the composite nano material is 1 nm to 30 nm.

4. A method for preparing a positive electrode material for a battery, characterized in that: include: Etching MAX phase powder to obtain V2CT x ; The V2CT x After mixing with an oxidant, a carbon-doped vanadium oxide is obtained, and the carbon-doped vanadium oxide is annealed in a reducing atmosphere to obtain a battery positive electrode material. The battery positive electrode material includes a composite nanomaterial of vanadium trioxide and carbon. The composite nanomaterial includes a heterojunction formed by vanadium trioxide and carbon, and the vanadium trioxide belongs to the trigonal crystal system.

5. The preparation method according to claim 4, characterized in that: The reducing atmosphere includes hydrogen.

6. The preparation method according to claim 4, characterized in that: The oxidant comprises hydrogen peroxide; the V2CT x The mass ratio of the hydrogen peroxide to the hydrogen peroxide is 1:(0.5-5).

7. The preparation method according to claim 4, characterized in that: The temperature of the annealing treatment is 700° C. to 1000° C., and the time of the annealing treatment is 0.5 h to 4 h.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The preparation method further comprises: freeze-drying the carbon-doped vanadium oxide before the annealing treatment.

9. A secondary battery, characterized in that: It comprises a positive electrode, a negative electrode, an electrolyte and a separator located between the positive electrode and the negative electrode, wherein the positive electrode comprises the battery positive electrode material as described in any one of claims 1 to 3 or the battery positive electrode material obtained by the preparation method as described in any one of claims 4 to 8.

10. An electronic device, characterized in that: The electronic device includes the secondary battery according to claim 9.

Citation Information

Patent Citations

  • Preparation method for vanadium oxide composite electrode material used for zinc ion battery

    CN107221665A